EFFECT OF WATER STRESS ON GROWTH, METABOLIC ACTIVITIES OF WITHANIA SOMNIFERA-AN IMPORTANT PHYTOCEUTICAL PLANT: AMELIORATIVE EFFECTS OF VAM - Haripriya M (Journal of Global Pharma Technology, 2010)
A greenhouse experiment was conducted to study the influence of arbuscular mycorrhizal (VAM) fungus inoculation on Withania somnifera, a medicinal plant under water stress. Root and Shoot lengths, total plant dry and fresh weights, root and shoot dry and fresh weights, number of leaves, leaf area, chlorophyll content, lipid content, carbohydrate content, DNA and RNA content were evaluated at 12 days, 20 days and 28 days after stress. Study of all the above parameters was made in four treatments T1 (control), T2 (mild stress), T3 (severe stress), T4 (severe stress with VAM treatment). We observed in all the characteristic features of the study, that there was a decrease in them during severe stress conditions compared with those of control plants. The VAM treatment helped the plants to with stand the water stress and to yield maximum biomass.Keywords: Water stress, growth, biochemical aspects, Withania somnifera.